THE RELEVANCE OF HISTORY IN THE GENERAL STUDIES PROGRAM OF UNIVERSITY OF SCIENCE AND TECHNOLOGY (Paramita: Historical Studies Journal, 2018)
This paper examines the relevance of the discipline of the history to the study of science and Technology in Nigeria. It interrogates how historical memories have shaped the discipline of science with respect to innovation, creativity and technological advancement for the progress of human society. Studying the historical biographies of scientists and the contributions of Africans to the understanding of science in the General studies program has helped to initiate and to develop critical thinking and inquiry on the possibility of improving untapped areas for technological advancement. The teaching of important memorable scientific achievement of the past has helped to shape the understanding of the present challenges. The paper concludes that the historical knowledge of science and technology of human society in Nigeria is a necessity to achieving positive development for human existence.Â Makalah ini meneliti relevansi disiplin sejarah untuk mempelajari ilmu dan teknologi di Nigeria. Di dalamnya dianalisis bagaimana kenangan sejarah telah membentuk disiplin ilmu sehubungan dengan inovasi, kreativitas dan kemajuan teknologi untuk kemajuan masyarakat manusia. Mempelajari riwayat biografi para ilmuwan dan kontribusi orang Afrika untuk memahami sains dalam program studi umum telah membantu untuk memulai dan mengembangkan pemikiran kritis dan penyelidikan tentang kemungkinan meningkatkan daerah yang belum dimanfaatkan untuk kemajuan teknologi. Ajaran penting pencapaian ilmiah yang mengesankan dari masa lalu telah membantu membentuk pemahaman tentang tantangan saat ini. Makalah ini menyimpulkan bahwa pengetahuan historis sains dan teknologi masyarakat manusia di Nigeria adalah suatu keharusan untuk mencapai perkembangan positif bagi eksistensi manusia.Â